Future intentions of residents regarding the celebration of Formula E in Santiago de Chile - Duclos-Bastías, Daniel; Parra-Camacho, David; Giakoni-Ramírez, Frano; Ulloa-Hernández, Maira; Sánchez Sáez, Juan Antonio (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The social impact of sporting events has been analysed mainly through residents' perceptions. The aim of this study was to find out residents' future intentions about the celebration of the 2018 Formula E Grand Prix of Santiago de Chile. For the selection of the sample (n=414 residents) the non-probability purposive sampling method was used with a confidence interval of 95%. The instrument used was an online questionnaire with a Likert scale (five-point scale). The results offered values close to four, which would indicate a positive trend in the residents' intentions. On the other hand, the significant influence of various socio-demographic variables related to the celebration of the event was verified: age, sex, studies, ideology, occupation, family residence, support for the celebration, attendance and employment ties with the sector. The results of the study made it possible to establish a favourable social perception of the reception of the event, although with different levels depending on the social group and its link to the event.